1985
DOI: 10.1016/s0092-8674(85)80099-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel force-generating protein, kinesin, involved in microtubule-based motility

Abstract: SummaryAxoplasm from the squid giant axon contains a soluble protein translocator that induces movement of microtubules on glass, latex beads on microtubules, and axoplasmic organelles on microtubules. We now report the partial purification of a protein from squid giant axons and optic lobes that induces these microtubule-based movements and show that there is a homologous protein in bovine brain. The purification of the translocator protein depends primarily on its unusual property of forming a high affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
1,192
4
5

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,851 publications
(1,240 citation statements)
references
References 40 publications
39
1,192
4
5
Order By: Relevance
“…Kinesin-1, the first kinesin to be discovered [79], is a tetrameric protein consisting of two identical heavy chains of Mr 120 000 and two identical light chains of Mr 64 000 (Figure 2) [80]. The mammalian genome contains three kinesin-1 heavy chain (KHC) genes (KIF5A, KIF5B and KIF5C) and three kinesin-1 light chain (KLC) genes (KLC1, KLC2, KLC3) [12].…”
Section: Kinesinmentioning
confidence: 99%
“…Kinesin-1, the first kinesin to be discovered [79], is a tetrameric protein consisting of two identical heavy chains of Mr 120 000 and two identical light chains of Mr 64 000 (Figure 2) [80]. The mammalian genome contains three kinesin-1 heavy chain (KHC) genes (KIF5A, KIF5B and KIF5C) and three kinesin-1 light chain (KLC) genes (KLC1, KLC2, KLC3) [12].…”
Section: Kinesinmentioning
confidence: 99%
“…These results suggest that most interesting to test those dyneins that are capable of tubulin also binds to the A end of the arm, an interaction functionally rebinding to axonemes [Gibbons and Gibthat should not be dissociated by ATPhanadate. The bons, 1978;Yano and Miki-Noumura, 19811 for their observation that high-salt treatment does not usually ex-ability to promote latex bead movements [Sheetz and tract all dynein arms from axonemes is consistent with Spudich, 1983;Vale et al, 1985a-cl along in vitro-assemthe observed failure of this treatment to disrupt com-bled microtubles versus individual outer doublets. Such pletely the interaction of dynein and tubulin.…”
Section: Tubulin Promotes An Apparent Interaction Between the A Ends mentioning
confidence: 99%
“…The microtubule motor protein kinesin, also known as conventional kinesin, was identified in 1985 (1,2) as the motile force underlying movement of particles along the microtubules of the giant axon of the squid. (3)(4)(5) Kinesin was shown to be capable of binding to microtubules and, in the presence of ATP, of moving towards the fast polymerizing/depolymerizing plus ends of microtubules, (6) representing the first cytoplasmic microtubule motor protein to be discovered.…”
Section: Introductionmentioning
confidence: 99%